Opening Government Transparency and Engagement in the Information Age - Wanna, John; Vincent, Sam (ANU Press, 2018)
"Transparency and citizen engagement remain essential to good government and sound public policy. Indeed, they may well be the key to restoring trust in government itself, currently at an all-time low in Australia. It is ironic, then, that this has occurred at a time when the technological potential for information dissemination and interaction has never been greater. Opening Government: Transparency and Engagement in the Information Age explores new horizons and scenarios for better governance in the context of the new information age, focusing on the potentials and pitfalls for governments (and governance more broadly) operating in the new, information-rich environment. Its contributors, a range of international and Australian governance academics and practitioners, ask what are the challenges to our governing traditions and practices in the new information age, and where can better outcomes be expected using future technologies. They explore the fundamental ambiguities extant in opening up government, with governments intending to become far more transparent in providing information and in information sharing, but also more motivated to engage with other data sources, data systems and social technologies."